Reflections on Linguistic and Literary Colonization and Decolonization in Africa - Eric Sellin (Studies in 20th & 21st Century Literature, 1991)
Despite the cultural diversity found in Africa and the complexity ofthe psychology of the colonizer and the colonized, several fundamental facts emerge regarding the function of language and literature in recent African history. The colonizer sought to instill a sense of inferiority in the colonized as part of the dynamics of conquest, placing special emphasis on education and language. These notions, lucidly discussed by such social thinkers as O. Mannoni, Frantz Fanon, and Albert Memmi, have analogues in the defense of language everywhere where lingua-political oppression occurs, be it in colonial Africa or on an Arapaho reservation in the American West. What is especially significant about the forced acquisition of a European language is the fact that this very tool of oppression tended to become the total of unity and rebellion for the oppressed. From a political viewpoint, the acquisition of a European lingua-franca entailed such logistics of liberation as communication and collective identity which overrode regional and tribal differences. From a cultural viewpoint, the language which had been used to colonize the minds of Africans knew two phases: first, one of simple acquisition of both language and attendant literary forms and second, one in which the European language was warped or "bullied" to fit the author's African cultural impulses. In the second instance we have, as a result of code-mixing and the transfer of cultural factors, the emergence of a unique and vigorous literature. In itself, this literature may be appreciated qua literature, but we should not forget that the code-mixing is often as concerned with the rejection of the language of oppression and the restauration of indigenous values as it is with traditional literary self-expression, as, for example, in the two poems by Algerian poet Youcef Sebti which bear the titles "La Soleil" and "Le Lune," thereby pooh-poohing sacrosanct French grammar by reversing the genders of "sun" and "moon" even as the articles reinstate the respective feminine and masculine genders of "sun" and "moon" found in Arabic.
Keywords: cultural diversity; Africa; culture; psychology; colonizer; colonized; language; literature; recent; history; African; inferiority; education; O. Mannoni; Frantz Fanon; Albert Memmi; lingua-politicalm; oppression; colonial Africa; colonial; Arapaho reservation; American West; forced acquisition; European language; acquisition; lingua-franca; European lingua-franca; communication; collective identity; regional; tribal; differences; cultural; bullied; code-mixing; qua literature; rejection; indigenous values; self-expression; Algerian; Youcef Sebti; La Soleil; Le Lune; French grammar; French; gender; Arabic